O corso na segunda metade do século XVIII : reflexos de um cartório notarial portuense - Ferreira, Sérgio (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This paper aims at contributing to a greater understanding of the different realities sustaining privatization actions during the second half of the 18th century. The study comprehends the political involvement and legal framework, practical procedures and material aspects, as well as the intellectual context which emerged, reflecting an exceptional historical moment. In this sense, a number of issues will be addressed, such as the neutrality of the seas, the strategies of privatization approaches, detention and trial of prisoners, as well as the behaviour of the victims, in an attempt to capture, at this level, the world revolving around the emotions, skills and values of the 18th century seafaring man.